Simulation of lithium-ion battery architectures - Lukman Umar Zainal. (2010)
Battery models for simulation are useful for estimating operating life, stability and related characteristics of batteries used in systems and circuits. Batteries with interpenetrating electrode architectures have the potential to outperform classical designs. These electrode structures are highly percolating particle distributions with short diffusion distances. One of the main advantages with respect to classic rocking chair battery designs are the decrease of the ohmic losses and localized joule-heating. This simultaneously delivers higher power densities and specific energies closer to the theoretical ideal. In this report, the rocking chair lithium-ion battery architecture is taken as a point of reference to explore two variations of a three-dimensional battery concept. In this report, the author developed a lithium-ion battery model from the mathematical equations given in a reference book [1]. Simulations using Object Oriented Finite Element Model were attempted. The two variations were found to outperform the classical rocking chair battery design at intermediate and higher discharge rates.